Pengaruh Penerapan Metode Talaqqi Terhadap Tingkat Kemampuan Menghafal Al-Qur’an Peserta Didik di SMP Muhammadiyah Gandrungmangu Cilacap - Ainun Robani; Siti Kholidatur Rodiyah (STIKes Ibnu Sina Ajibarang, 2024)
The programme Tahfidzul Qur'an program at Muhammadiyah Gandrungmangu Middle School, Cilacap, which every year always schedules its students to become tarawih prayer leaders at several mosques in the area around the school. This tahfidzul Qur'an program is implemented using the Talaqqi method. The aim of this research is to find out how the Talaqqi method is applied in the Al-Qur'an memorization program at Muhammadiyah Gandrungmangu Middle School Cilacap, to find out the level of students' ability to memorize the Al-Qur'an at Muhammadiyah Gandrungmangu Middle School Cilacap, and to find out what the effect of applying the method is. Talaqqi on students' ability to memorize the Al-Qur'an at Muhammadiyah Gandrungmangu Middle School, Cilacap. The research method used is quantitative research with a correlation approach. The sample in this research were all Muhammadiyah Gandrungmangu Cilacap Middle School students because it was a population study. The variable X is the application of the talaqqi method. Meanwhile, the Y variable is the level of ability to memorize the Al-Qur'an of students at Muhammadiyah Gandrungmangu Middle School, Cilacap. The data collection technique uses questionnaires, tests and documentation. The results of this research obtained from the data analysis carried out, it was found that the level of application of the talaqqi method in the Al-Qur'an memorization program for Muhammadiyah Gandrungmangu Cilacap Middle School students was 86.9%, in the range of 81% to 100%, classified as